Altered significance of D'Amico risk classification in patients with prostate cancer linked to a familial breast cancer (kConFab) cohort. (6th April 2015) - Bolton, Damien; Cheng, Yuan; Willems‐Jones, Amber J.; Li, Jason; Niedermeyr, Eveline; Mitchell, Gillian; Clouston, David; Lawrentschuk, Nathan; Sliwinski, Ania; Fox, Stephen; Thorne, Heather
<x xml:space="preserve">Abstract</x> Objective To ascertain whether D'Amico risk classification is an accurate discriminator of prostate cancer mortality risk in BRCA2 pathogenic mutation carriers and non‐carriers from a familial breast cancer cohort. Patients and Methods From family cancer pedigrees of patients evaluated through a familial breast cancer cohort all related men with a diagnosis of prostate cancer were identified. Genotyping of each patient or of the dominant familial BRCA2 mutation was undertaken in each instance. Prostate cancers were analysed by BRCA2 carrier vs non‐carrier status for their clinical progression and survival according to their D'Amico risk groups. Results For patients who were BRCA2‐mutation positive, there was no significant difference in cancer‐specific survival (CSS) between those patients who were graded as having D'Amico high‐ or intermediate‐risk disease. For patients who were BRCA2‐mutation negative, but were identified via a family cancer pedigree, there was no statistically significant difference in CSS between D'Amico high‐ and intermediate‐risk prostate cancers. Patients with D'Amico high‐risk disease who were BRCA2‐mutation carriers had substantially increased disease‐specific mortality compared with high‐risk non‐carriers (hazard ratio 2.94, P = 0.004). Conclusion D'Amico risk classification has limitations in predicting variations in prostate cancer‐specific mortality for this group of patients.